Characterization and Antimicrobial Susceptibility of Lactococcus lactis Isolated from Endodontic Infections in Ouagadougou, Burkina Faso - Kaboré, Wendpoulomdé Aimé Désiré (Dent J (Basel), 2018)
Background: This study aimed to characterize and test the antimicrobial susceptibility of Lactococcus lactis isolated in endodontic infections in Burkina Faso. Material and methods: This was a prospective study conducted at the Municipal Oral Health Center of Ouagadougou, Burkina Faso, from June to October 2014. Clinical data were collected using a questionnaire form. The method of streaking on selective medium was used to isolate bacteria. Identification was made using the API 20 Strep gallery. Antibiotic susceptibility was performed by the diffusion method on solid medium. Results: One hundred and twenty-five (125) patients were received with a significant proportion from the age group of 19 to 40 years (55.2%). Apical periodontitis accounted for 50.4% and cellulitis for 49.6% of cases. Lactococcus lactis ssp. lactis was identified in five exudate samples. Isolates were 100% resistant to cefixime and metronidazole, 80% to ceftriaxone, cefuroxime, cefotaxime, chloramphenicol and 60% to penicillin G, amoxicillin, amoxicillin clavulanic acid. A multidrug resistance of more than three families of antibiotics was noticed. No strains produced extended spectrum ß-lactamases. Conclusion: Lactococcus lactis is part of endodontic biofilm. The reported strong antibiotic resistance involving endodontic therapy will focus on the effect of the disinfectant solution and the mechanical action of the canal instruments.